(untitled) (Global Journal of Medical Research, 2021)
Background: Denture stomatitis is one of the common fungal infections that manifests over the edentulous ridges bearing dentures in patients using dentures. Commercially various synthetic substitutes are used for treatment of denture stomatitis. Various in-vitro studies showed that Punica granatum (Pomegranate) fruit is rich in nutraceutical